2022
DOI: 10.3390/molecules27238196
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Spirotetronate Polyketides from an Actinomadura sp. Strain A30804

Abstract: Large scale cultivation and chemical investigation of an extract obtained from Actimonadura sp. resulted in the identification of six previously undescribed spirotetronates (pyrrolosporin B and decatromicins C–G; 7–12), along with six known congeners, namely decatromicins A–B (1–2), BE-45722B–D (3–5), and pyrrolosporin A (6). The chemical structures of compounds 1–12 were characterized via comparison with previously reported data and analysis of 1D/2D NMR and MS data. The structures of all new compounds were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…51 Additional analogues of this spirotetronate compound series (28)(29)(30)(31)(32)(33)(34)(35), along with those previously reported (24)(25)(26)(27), were isolated from culture extracts of Actinomadura strain A30804. 52 Structure-activity relationship studies of this set of compounds suggested that the presence of at least two chloro-substitutions on the pyrrole ring is important for antibacterial activity. 52 Spirotetronate kijanimicin (36), produced by A. kijaniata, has a broad spectrum of antimicrobial activity against several Grampositive bacteria, anaerobes, P. falciparum, and also exhibited antitumor activity in a mouse lymphatic leukaemia model.…”
Section: Spirotetronatesmentioning
confidence: 94%
See 3 more Smart Citations
“…51 Additional analogues of this spirotetronate compound series (28)(29)(30)(31)(32)(33)(34)(35), along with those previously reported (24)(25)(26)(27), were isolated from culture extracts of Actinomadura strain A30804. 52 Structure-activity relationship studies of this set of compounds suggested that the presence of at least two chloro-substitutions on the pyrrole ring is important for antibacterial activity. 52 Spirotetronate kijanimicin (36), produced by A. kijaniata, has a broad spectrum of antimicrobial activity against several Grampositive bacteria, anaerobes, P. falciparum, and also exhibited antitumor activity in a mouse lymphatic leukaemia model.…”
Section: Spirotetronatesmentioning
confidence: 94%
“…52 Structure-activity relationship studies of this set of compounds suggested that the presence of at least two chloro-substitutions on the pyrrole ring is important for antibacterial activity. 52 Spirotetronate kijanimicin (36), produced by A. kijaniata, has a broad spectrum of antimicrobial activity against several Grampositive bacteria, anaerobes, P. falciparum, and also exhibited antitumor activity in a mouse lymphatic leukaemia model. [53][54][55][56][57] The aglycone of kijanimicin is decorated with three L-digitoxose moieties and a rare nitro sugar, D-kijanose.…”
Section: Spirotetronatesmentioning
confidence: 94%
See 2 more Smart Citations
“…Alkaloids make up one of the most significant categories of natural products isolated from marine environments [ 15 ]. Among marine alkaloids, pyrroles are a large group of interesting natural products which occur in marine environments, ranging from microorganisms to algae, sponges, and animals [ 16 , 17 , 18 ]. Pyrroles possess a flat and electron-rich aromatic ring, and their structure is susceptible to electrophilic attack and can also interact with a variety of biomolecules via hydrogen bonds as well as π–π stacking interactions [ 19 ].…”
Section: Introductionmentioning
confidence: 99%